Dose-rate conversion factors: update - Adamiec, G.; Aitken, M. J. (Ancient TL, 1998)
Dose-rate conversion factors relevant to luminescence dans electron spin resonance dating have been derived from values for the energy carried by radiations emitted during nuclear transformations given in the current ENSDF (Evaluated Nuclear Structure Data File). For beta and gamma radiation the factors are a few percent lower than previously used for the effetive alpha dose-rate it is more appropriate to use an approach based on particle anges and resultant values are given.